Infuence of aluminium and tungsten impurities on reduced graphene oxide/zinc oxide nanocomposites humidity sensing performance - A. Shamsul Rahimi A. Subki; Faiz Arith; Dayana Kamaruzaman; Norfarariyanti Parimon; Musa Mohamed Zahidi; Suriani Abu Bakar; Mohd Khairul Ahmad; Muhammad Danang Birowosuto; Nagamalai Vasimalai; Mohamad Hafz Mamat (Springer Nature, 2025)
In this work, impurities-induced ZnO nanostructured powders were prepared via a benign, ultrasonicated low-temperature solution immersion method. The humidity sensor was constructed utilizing the nanocomposite consisting of the synthesized impurities-induced ZnO nanostructured powders with reduced graphene oxide by a facile brush printing procedure. This work intended to evaluate the efect of impurities on the formation of nanocomposite heterostructures for optimal humidity sensing properties and investigate their correlation with morphological, chemical, optical, and electrical characteristics. The characterization for morphological, chemical, and optical changes induced by Al and W impurities in the nanocomposites was conducted through XRD, HRTEM, EDS, Raman spectroscopy, XPS and DRS. The fabricated humidity sensors have been evaluated at room temperature to assess their sensor resistance ratio, sensitivity, sensing response, and other related humidity sensing performance at relative humidity levels ranging from 40 to 90%. The humidity sensor utilizing rGO/W:ZnO nanocomposite exhibited better resistance changes compared to rGO/ZnO. Corresponding to the nanocomposite formation between W:ZnO and rGO, the sensor resistance ratio and sensitivity improved signifcantly to 249.61±0.97 and 12.67±0.06 MΩ/%RH, respectively with the sensor establishing a maximum sensing response of 99.61±0.02. Furthermore, the rGO/W:ZnO heterostructure-based humidity sensor demonstrated improved and lowest hysteresis error, long-term stability over 30 days, and reliable repeatability compared to other tested samples within the tested relative humidity range. The utilization of W:ZnO with rGO as sensing material provides a novel direction for designing a cost-efective and highly sensitive humidity monitoring sensor.